A CLEWS Nexus modeling approach to assess water security trajectories and infrastructure needs in Latin America and the Caribbean - Raúl Mu\~noz-Castillo; Fernando Miralles-Wilhelm; Kleber Machado (Inter-American Development Bank (IDB), 2019)
This working paper presents an up-to-date and prospective assessment of water security throughout the Latin America and Caribbean (LAC) region, with a focus on infrastructure needs, to aid in strategic thinking towards planning and management in key water-using sectors such as agriculture, energy and water supply. This assessment is grounded on a physically-based analysis of water supply and demand, highlights the climate-land-energy-water-socioeconomics (CLEWS) nexus contributions to water security in the region and addresses uncertainty in projections and their implications through a variety of potential future scenarios of climate change and socioeconomic development in the region. This investigation can be thought of as an exercise of envisioning possible futures of water security for the LAC region, explaining existing vulnerabilities when it comes to CLEWS nexus and laying out water infrastructure needs for addressing current and likely future problems under a range of such scenarios. The analysis that leads to estimates of infrastructure needs in the water sector is based on a multi-sector nexus approach that is at the core of the methodology employed in computing water supply and demand. This is both an important distinction and a contribution of this research compared to traditional single-sector approaches to assess projected water demands and associated infrastructure needs. By providing a socioeconomic quantitative framework for integrated analysis of water supply and demand, climate scenarios, and other forcing factors such as land use change and technological developments, this research can be extended to analytically explore different types of policy and investment interventions in multiple water demand sectors.
Keywords: Q24; Q25; Q40; O18; 330; water; energy; land; nexus; infrastructure; water security; Latin America and the Caribbean